Peripheral arterial embolization and limb ischemia complicating septic internal jugular vein thrombosis: a case report of Lemierre’s syndrome - Vojko Flis; Zvonko Borovšak (Acta Medico-Biotechnica, 2021)
Purpose: Septic thrombophlebitis of the internal jugular vein is a life-threatening complication of venous thrombosis. While heparin is frequently added to antimicrobial therapy, its usefulness in patients with Lemierre’s syndrome is controversial. In this case report, we demonstrate that delayed use of intravenous heparin may be associated with septic embolization of peripheral arteries. Limb ischemia has rarely been reported in patients with Lemierre’s syndrome.Case presentation: Lemierre’s syndrome is a complex and unusual clinical entity, characterized by septic thrombophlebitis of the internal jugular vein and accompanied by sepsis. We present an unusual case of a young female with Lemierre’s syndrome who developed peripheral arterial embolization and Streptococcus pyogenes sepsis, complicating septic internal jugular vein thrombosis. The patient was initially treated with antibiotics without therapeutic heparin. The patient developed digital gangrene in all four extremities, septic meningitis, and a severe fungal infection; she died 6 weeks after admission secondary to multisystem organ failure. We discuss the importance of rapid diagnosis of disease extent in directing heparin treatment in patients with Lemierre’s syndrome.Conclusion: It may be advisable to treat Lemierre’s syndrome with anticoagulation in the acute setting.